2010
DOI: 10.1002/pi.2817
|View full text |Cite
|
Sign up to set email alerts
|

Surface morphology, thermomechanical and barrier properties of poly(ether sulfone)‐toughened epoxy clay ternary nanocomposites

Abstract: Poly(ether sulfone) (PES)‐toughened epoxy clay ternary nanocomposites were prepared by melt blending of PES with diglycidyl ether of bisphenol A epoxy resin along with Cloisite 30B followed by curing with 4,4′‐diaminodiphenylsulfone. The effect of organoclay and thermoplastic on the fracture toughness, permeability, viscoelasticity and thermomechanical properties of the epoxy system was investigated. A significant improvement in fracture toughness and modulus with reduced coefficient of thermal expansion (CTE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…In our earlier studies, we have observed significant improvement in fracture toughness, modulus and thermal stability and reduction in gas permeability and CTE for thermoplastic (PEEKMOH and PES) toughened epoxy clay ternary nanocomposites [28][29][30][31]. The present study deals with the preparation and evaluation of surface morphology, mechanical and thermo mechanical properties of PEEKMOH toughened epoxy hybrid syntactic foam containing glass microballoon as hollow filler and Cloisite 30B as nanofiller.…”
Section: Introductionmentioning
confidence: 93%
“…In our earlier studies, we have observed significant improvement in fracture toughness, modulus and thermal stability and reduction in gas permeability and CTE for thermoplastic (PEEKMOH and PES) toughened epoxy clay ternary nanocomposites [28][29][30][31]. The present study deals with the preparation and evaluation of surface morphology, mechanical and thermo mechanical properties of PEEKMOH toughened epoxy hybrid syntactic foam containing glass microballoon as hollow filler and Cloisite 30B as nanofiller.…”
Section: Introductionmentioning
confidence: 93%
“…This effect was observed in both immiscible thermoplastic systems [7][8][9] and epoxies with two phase structures formed by the reaction-induced phase separation (RIPS) [10] of a modifier dissolved in an uncured resin. The enhanced mechanical performance of epoxy systems was mostly observed in liquid rubbers and clays [11][12][13] and in combinations of thermoplastics (PEEK, PEI, PES, ABS) and clays [14][15][16][17][18][19][20]. The synergistic effect of the nanofiller consists in its complex effect on the multiphase system by reinforcement, leading also to a change in the component parameter profile combined with a significant influence on the structure and parameters of the interface.…”
Section: Introductionmentioning
confidence: 99%
“…The polar amino or cyano functional groups of the organic moiety of the clay can enhance interfacial adhesion through the chemical bonding interaction between the PAEK‐CN matrix and the clay. The matrix/composites become less brittle in comparison with the neat phthalonitrile resin because physical separation of the clay platelets reduces their crosslink density . Many open‐cell regions can be observed in Fig.…”
Section: Resultsmentioning
confidence: 99%